Immoderation: comparing the Christian Right in the US and pro-Islamic movement-parties in Turkey. Issue 3 (15th April 2016) - Kirdiş, Esen
Abstract : This article will discuss the "immoderation" of religious political actors – defined as the continuation of a relatively closed and rigid worldview – through a cross-religious comparison of the Christian Right coalition within the Republican Party in the US with the pro-Islamic movement-parties in Turkey. By adapting a "most different systems approach", this study will question the similar evolution of two religious political actors in two dissimilar political regimes. In particular, it will question the processes and types of immoderation by looking into (1) "behavioural immoderation", immoderation for the strategic purpose of forming a small yet ideologically pure supporter base, and into (2) "ideological immoderation", immoderation as a result of a continued advocacy for a moral role for the state without a full embrace of political pluralism. In this, it will argue that religious political actors are strategic actors who try to guarantee their organizational survival amidst changing costs and benefits of moderation vis-à-vis immoderation. Through its discussion of "immoderation" and through its cross-religious comparison, this study will aim to contribute to the inclusion-moderation literature.